Art as knowledge: situational geography of the borderlines (KULT_online, 2014)
The book is a collection of travel notes, diaries, expressions of activists’ opinions, event reports, and encyclopedia excerpts on the organizations involved in border management. It is a type of intriguing clipboard, one in which articles are given more relaxed formats with small-cap titles and a maximum length of five pages.This book creates the potential for a multiplicity of layers through which the topic of borders and border crossing could be approached. One could associate this book with the field of situational geography, the study of interaction of human and natural complexities organized around the descriptive research of different sites, in this case – borders. This unique mix offers readers an opportunity to connect border-related themes that perhaps would not otherwise have been integrated into a dialog with each other. An analysis of this network of ideas is not predetermined, however, so the reader is encouraged to discover the potential themes him or herself.Without a profound theoretical framework, this book is mainly based on personal experiences, art projects, and the well-stated political opinions of the contributors. It is a genuine invitation to explore the potential of the topic, criticizing the existing systems and questioning the state of politics that prevails in border management, particularly in the EU.